Unidentified γ-ray sources off the Galactic plane as low-mass microquasars? - Grenier, I. A. (2005)
A subset of the unidentified EGRET γ -ray sources with no active galactic nucleus or other conspicuous counterpart appears to be concentrated at medium latitudes. Their long-term variability and their spatial distribution indicate that they are distinct from the more persistent sources associated with the nearby Gould Belt. They exhibit a large scale height of 1.3 ± 0.6 kpc above the Galactic plane. Potential counterparts for these sources include microquasars accreting from a low-mass star and spewing a continuous jet. Detailed calculations have been performed of the jet inverse Compton emission in the radiation fields from the star, the accretion disc, and a hot corona. Different jet Lorentz factors, powers, and aspect angles have been explored. The up-scattered emission from the corona predominates below 100 MeV whereas the disc and stellar contributions are preponderant at higher energies for moderate (∼15◦) and small (∼1◦) aspect angles, respectively. Yet, unlike in the highmass, brighter versions of these systems, the external Compton emission largely fails to produce the luminosities required for 5 to 10 kpc distant EGRET sources. Synchrotron-self-Compton emission appears as a promising alternative.